Analisis Intensitas Kebisingan di Jalan Lintas Padang-Bukittinggi: Studi Kasus Pasar Lubuk Alung, Kabupaten Padang Pariaman - Dilla, Nadia Ulfa; Chandra, Deded (TSAQOFAH, 2026)
This study aims to analyze noise levels along the Padang–Bukittinggi arterial road, with a specific focus on the Lubuk Alung Market area in Padang Pariaman Regency, which is characterized by high traffic intensity and community mobility, thereby creating noise that has the potential to reduce environmental comfort and endanger public health when its intensity exceeds established quality standards. The research employs a descriptive quantitative approach with purposive sampling at three strategic measurement points. Primary data were obtained by measuring noise intensity using a sound level meter with five-second recording intervals over ten minutes in the morning, at midday, and in the afternoon, both on working days and holidays. The data were processed using Microsoft Excel and spatially analyzed through Inverse Distance Weighting (IDW) interpolation in ArcGIS 10.3. The results show that all measurement points exhibit high noise levels, with the highest values recorded at Point 2, which consistently exceeded 79 dBA, as well as a tendency for increased noise intensity at midday and in the afternoon in line with higher levels of human and vehicular activity. These findings underscore the need for noise mitigation strategies, such as traffic management, spatial zoning, and the installation of acoustic barriers, to create a healthier and more comfortable environment for residents in the Lubuk Alung Market area.